Malaysia - Productivity and Investment Climate Assessment Update - World Bank (World Bank, 2012)
In the decades prior to the Asian financial crisis, the Malaysian economy experienced rapid growth and a significant structural transformation. It went from an economy that relied on agriculture and commodities to one dominated by manufacturing and services. Since then, however, Malaysia's growth has slowed to a level well below its key competitors in Asia, including the large labor-surplus economies of China and India. The economy seems to be caught in a middle-income trap, unable to remain competitive as a high-volume, low-cost producer and unable to move up the value chain and achieve rapid growth by breaking into fast growing markets for knowledge, and innovation-based products and services. The Malaysian authorities have expressed their commitment to regain their earlier growth and reposition their economy as a rapidly growing, knowledge-based, high value-added and high income economy. A key element of their strategy is to encourage Malaysians to invest more of their savings at home, instead of abroad. Equally important is the need to improve the quality of that investment. As part of this effort, the Economic Planning Unit (EPU) of the Prime Minister's Department launched a second Malaysia Productivity and Investment Climate Survey in 2007 (PICS-II) to assess whether and how the investment environment had changed since the first survey in 2002 (PICS-I). This report presents the analytical results of the second survey, which covers nine manufacturing industries and five selected business support services industries.